Factors influencing perception of psychosocial risk among health workers at roemani muhammadiyah hospital - Rahmila, Septa; Denny, Hanifa Maher; Dewi, Endah Kumala (Jurnal Konseling dan Pendidikan, 2025)
Psychosocial risks in hospitals affect health workers mental and emotional well-being. These risks include violence, conflict, harassment, bullying from staff, patients, or visitors, and stress caused by shift work, excessive workload, monotony, and high job demands. Such risks can negatively impact health, productivity, and work efficiency. This study aims to analyze the most influential variables between interpersonal communication, working time and workload on the perception of psychosocial risk among health workers at Roemani Muhammadiyah Hospital, Semarang City. This research method is quantitative with a cross sectional design. The sampling technique used proportional stratified random sampling with a total sample of 82 health workers. The data collection technique uses a questionnaire that has been tested for validity and reliability.  The variables studied in this study include level of education, age, length of service, interpersonal communication, personal experience, working time, and workload. The data was processed and analyzed descriptively, as well as hypothesis testing using the chi-square test to see what variables were related to health workers psychosocial risk perceptions and logistic regression analysis to see which variables had the most influence on health workers psychosocial risk perceptions. The research results showed that the majority of respondents had a DIII education, most were adults, namely 22-44 years and most of the respondents had worked for more than 10 years. Variables that are related (p-value < 0.05) to the perception of psychosocial risk among health workers at Roemani Muhammadiyah Hospital, Semarang City are interpersonal communication, personal experience, workload and working time. The variable that has the greatest influence on the perception of psychosocial risk among health workers at Roemani Muhammadiyah Hospital, Semarang City is the interpersonal communication variable which has an odds ratio (OR) of 17.883, which means that health workers who have good interpersonal communication are 17.883 times more likely to perceive positive psychosocial risk than respondents who have poor interpersonal communication.